2005
DOI: 10.3748/wjg.v11.i13.1929
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 gene polymorphisms are associated with progression of liver fibrosis in Caucasians with chronic hepatitis C infection

Abstract: In summary, these results confirm the hypothesis that TGF-beta1 polymorphisms are associated with fibrosis progression in Caucasians chronically infected with hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 50 publications
2
53
0
1
Order By: Relevance
“…Genomic DNA was extracted from peripheral blood cells using the QIAamp DNA Blood Mini extraction kit (Qiagen, Hilden, Germany). The primers, cycling conditions, and melting curve analysis were in referring to our previous publication (17). The fluorescencelabeled primers were obtained from Metabion (Metabion, Martinsried, Germany), and the common PCR-primers were synthesized at MWG-Biotech AG (Ebersberg, Germany).…”
Section: Tgfβ1 Gene Snp Analysis In Lightcycler Systemmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood cells using the QIAamp DNA Blood Mini extraction kit (Qiagen, Hilden, Germany). The primers, cycling conditions, and melting curve analysis were in referring to our previous publication (17). The fluorescencelabeled primers were obtained from Metabion (Metabion, Martinsried, Germany), and the common PCR-primers were synthesized at MWG-Biotech AG (Ebersberg, Germany).…”
Section: Tgfβ1 Gene Snp Analysis In Lightcycler Systemmentioning
confidence: 99%
“…The G→C transition at position 915 of the TGF-β1 signal sequence causes the amino acid sequence to change from arginine to proline in codon 25. A number of previous studies reported the association between this SNP and susceptibility to chronic HCV infection (14)(15)(16)(17)(18)(19)(20)(21). However, the currently available results are controversial.…”
Section: Introductionmentioning
confidence: 78%
“…1. Finally, 8 eligible studies including a total of 1,542 participants (910 cases and 632 controls) were identified (14)(15)(16)(17)(18)(19)(20)(21). A summary of the characteristics of each study, including first author, year of publication, ethnicity of cases and controls, genotyping methods, number of cases and Table I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Qi et al (2009) reported that the TGF-β1 -509 CC genotype was associated with hepatitis B virus-related HCC in a Chinese population. In another study, Wang et al (2005) reported that the C allele of TGF-β1 -509, but not the T allele, might play an important role in the progression of liver cirrhosis. The differences in these results may have been caused by different clinical characteristics and the different ethnic groups studied.…”
Section: Discussionmentioning
confidence: 99%